Vinyl silane-modified polylactic acid-based nonwoven fabric material, and preparation method and application thereof

CN120700649BActive Publication Date: 2026-10-27WUYI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510870801.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2026-10-27
Estimated Expiration
2045-06-26

AI Technical Summary

Technical Problem

但现有PLA地膜技术仍存在诸多不足:一方面,多层复合PLA地膜工艺复杂且需使用有毒粘合剂,存在二次污染风险;另一方面,二氧化硅改性PLA地膜虽能提升抗紫外性能,但存在填料团聚、工艺复杂等问题,影响材料性能

Benefits of technology

[0010]本发明提供的乙烯基硅烷改性聚乳酸基无纺布材料通过原料组合,在保持聚乳酸(PLA)环境友好特性的同时,显著提升了材料的耐候性、力学性能和加工稳定性。首先,乙烯基硅烷在PLA分子链上引入硅氧键(Si-O)和硅碳键(Si-C)等疏水性基团,这不仅大幅降低了材料表面能,有效阻隔水分渗透,还通过硅羟基(Si-OH)的水解-缩合动态平衡机制延缓了PLA主链的水解断裂,从而显著提高了材料的耐水解性和抗老化性能。其次,抗老化树脂颗粒中抗氧剂与PLA/PBAT的协同作用构建了双重防护体系:而己二酸丁二醇酯和对苯二甲酸丁二醇酯的共聚物(PBAT)的引入不仅改善了PLA的脆性,其柔性链段还与硅烷改性PLA形成微相分离结构,进一步分散应力并提高韧性。此外,上述多尺度协同改性策略,使材料兼具优异的力学性能、耐水性、持久耐候性和可生物降解特性,为农用地膜等户外应用提供了理想的解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005469822280000091
    Figure BDA0005469822280000091
  • Figure BDA0005469822280000101
    Figure BDA0005469822280000101
  • Figure BDA0005469822280000102
    Figure BDA0005469822280000102
Patent Text Reader

Abstract

The application discloses a kind of vinyl silane modified polylactic acid-based non-woven materials and its preparation method and application, preparation raw materials include: vinyl silane modified polylactic acid particles and anti-aging resin particles;The preparation raw materials of vinyl silane modified polylactic acid particles include: vinyl silane and polylactic acid resin;The preparation raw materials of anti-aging resin particles include: antioxidant, polylactic acid resin and copolymer of butylene adipate and butylene terephthalate.This application provides the vinyl silane modified polylactic acid-based non-woven material with biobased biodegradable polylactic acid as main body, avoids the microplastic pollution problem of traditional PE / PP mulch, while through vinyl silane graft modification, on the basis of retaining PLA biodegradability, greatly improve its hydrolysis resistance and anti-aging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mulch film materials technology, specifically to a vinylsilane-modified polylactic acid-based nonwoven fabric material, its preparation method, and its application. Background Technology

[0002] Plastic mulch films, as an important auxiliary material in modern agriculture, play a crucial role in moisture retention, heat preservation, cold protection, and pest control. However, traditional mulch films such as PE, PP, and PET, which are widely used, are susceptible to environmental factors during long-term use, exhibiting problems such as aging, whitening, cracking, and breakage. These not only make them difficult to recycle, but the microplastics formed from their further degradation can cause persistent pollution to farmland. To address this issue, polylactic acid (PLA), as a novel bio-based biodegradable material, has attracted considerable attention. Made from renewable plants such as corn and sugarcane, it possesses excellent environmental friendliness and biocompatibility, and can be completely degraded by microorganisms under composting conditions, effectively avoiding microplastic pollution. However, existing PLA mulch film technology still has several shortcomings: on the one hand, multi-layer composite PLA mulch films have complex processes and require the use of toxic adhesives, posing a risk of secondary pollution; on the other hand, while silica-modified PLA mulch films can improve UV resistance, problems such as filler agglomeration and complex processes affect material performance. Compared to traditional dense mulch films, non-woven mulch films, with their superior air and moisture permeability, effectively prevent seedling burn and condensation, showing promising application prospects. However, existing natural fiber-based non-woven mulch films are prone to bacterial diseases, and some synthetic fiber components still cause microplastic pollution; while surface UV-resistant treatment processes have drawbacks such as poor durability and significant pollution. Therefore, developing a non-woven mulch film material that combines excellent biodegradability, hydrolysis resistance, and processing performance has become a key technical challenge urgently needing to be addressed for sustainable agricultural development. Summary of the Invention

[0003] This invention aims to solve the aforementioned technical problems existing in the prior art. To this end, this invention proposes a vinylsilane-modified polylactic acid (PLA)-based nonwoven fabric material, its preparation method, and its applications. The vinylsilane-modified PLA-based nonwoven fabric material provided by this invention uses bio-based biodegradable PLA as its main component, avoiding the microplastic pollution problem of traditional PE / PP mulch films. Simultaneously, through vinylsilane grafting modification, its hydrolysis resistance and anti-aging properties are significantly improved while retaining the biodegradability of PLA.

[0004] This invention also proposes a method for preparing vinylsilane-modified polylactic acid-based nonwoven fabric materials.

[0005] This invention also proposes the application of vinylsilane-modified polylactic acid-based nonwoven materials in the preparation of biodegradable mulch films.

[0006] According to a first aspect of the present invention, a vinylsilane-modified polylactic acid-based nonwoven fabric material is provided, the raw materials for which include: vinylsilane-modified polylactic acid particles and anti-aging resin particles;

[0007] The raw materials for preparing the vinylsilane-modified polylactic acid particles include: vinylsilane and polylactic acid resin;

[0008] The raw materials for preparing the anti-aging resin particles include: antioxidants, polylactic acid resin, and copolymers of butylene adipate and butylene terephthalate.

[0009] According to a first aspect of the present invention, at least the following beneficial effects are achieved:

[0010] The vinylsilane-modified polylactic acid (PLA) nonwoven material provided by this invention significantly improves the material's weather resistance, mechanical properties, and processing stability while maintaining the environmentally friendly characteristics of PLA through raw material combination. First, vinylsilane introduces hydrophobic groups such as silicon-oxygen bonds (Si-O) and silicon-carbon bonds (Si-C) into the PLA molecular chain. This not only significantly reduces the material's surface energy and effectively blocks moisture penetration, but also delays the hydrolytic breakage of the PLA main chain through the hydrolysis-condensation dynamic equilibrium mechanism of silanol groups (Si-OH), thereby significantly improving the material's hydrolysis resistance and anti-aging properties. Second, the synergistic effect of antioxidants in the anti-aging resin particles and PLA / PBAT constructs a dual protection system: the introduction of the copolymer of butylene adipate and butylene terephthalate (PBAT) not only improves the brittleness of PLA, but its flexible segments also form a microphase separation structure with the silane-modified PLA, further dispersing stress and improving toughness. Furthermore, the aforementioned multi-scale synergistic modification strategy endows the material with excellent mechanical properties, water resistance, durable weather resistance, and biodegradability, providing an ideal solution for outdoor applications such as agricultural mulch films.

[0011] In some embodiments of the present invention, the copolymer of butylene adipate and butylene terephthalate is of spinning grade and has a melt index of 10 to 20.

[0012] In some embodiments of the present invention, the polylactic acid resin is of spinning grade and has a melt index of 10 to 20.

[0013] In some embodiments of the present invention, the antioxidant includes at least one of antioxidant 168, antioxidant 9228, antioxidant 1010, and antioxidant 1076.

[0014] In some embodiments of the present invention, the raw materials for preparing the vinylsilane-modified polylactic acid particles further include: an initiator and an anti-ultraviolet agent.

[0015] In some embodiments of the present invention, the initiator includes at least one of benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.

[0016] In some embodiments of the present invention, the UV protectant includes at least one of UV-329, UV-234, and UV-360.

[0017] In some embodiments of the present invention, the raw materials for preparation include, by weight: 20 to 100 parts of vinylsilane-modified polylactic acid particles and 1 to 80 parts of anti-aging resin particles.

[0018] In this invention, a formulation of 20–100 parts vinylsilane-modified polylactic acid particles and 1–80 parts anti-aging resin particles is employed, demonstrating significant advantages in material performance control. This ratio range first ensures the continuous phase advantage of vinylsilane-modified PLA as the matrix material, and its grafted siloxane structure effectively constructs a hydrophobic network, maintaining stable hydrophobic properties in the material.

[0019] In some embodiments of the present invention, the vinyl silane includes: readily hydrolyzable vinyl silane and non-hydrolyzable vinyl silane;

[0020] The readily hydrolyzable vinylsilanes include at least one of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, and vinyltriisopropoxysilane;

[0021] The non-hydrolyzable vinyl silanes include at least one of vinyl silicone oil, tetramethyltetravinylcyclotetrasiloxane, divinyltetramethyldisiloxane, vinyl silicone oil, and vinyltriisopropoxysilane.

[0022] In some embodiments of the present invention, the vinylsilane is, by weight ratio, a 1:1 to 3 ratio of readily hydrolyzable vinylsilane and not readily hydrolyzable vinylsilane.

[0023] The alkoxy groups (-OR) of readily hydrolyzable vinylsilanes partially hydrolyze during processing to generate silanol groups (Si-OH). These active groups can undergo grafting reactions with carboxyl or hydroxyl groups on the polylactic acid (PLA) molecular chain, constructing a stable Si-OC covalent bond network on the PLA backbone. This not only significantly improves the hydrophobicity of PLA, but more importantly, it forms a dynamic protection mechanism—when hydrolysis occurs during material use, the Si-OC bonds in the readily hydrolyzable silane preferentially break to generate new Si-OH. These silanol groups then reform Si-O-Si crosslinking points through condensation reactions, thereby delaying the breakage process of the PLA backbone.

[0024] Vinylsilanes, which are not easily hydrolyzed, form a hydrophobic barrier in the material due to their stable Si-O-Si and Si-C bond structures, effectively preventing the penetration of water molecules. They enhance the interaction forces between PLA molecular chains through physical entanglement. Furthermore, these silanes partially open their rings during melt processing, forming an interpenetrating network with the active ends of easily hydrolyzed silanes. This avoids the increased brittleness caused by excessive cross-linking of a single easily hydrolyzed silane and solves the problem of easy migration and precipitation of pure silicone oil.

[0025] The synergistic effect of the two: the easily hydrolyzable silane is activated by an initiator during twin-screw extrusion to achieve controlled grafting, while the non-hydrolyzable silane acts as a melt flow promoter to improve the spinning performance of PLA. The ethylene functional groups in vinyl silane are grafted onto the PLA main chain to prevent the precipitation of flexible silane during use. This "dynamic + static" dual protection system allows the material to cope with temperature and humidity changes through the "self-healing" properties of the easily hydrolyzable silane when used outdoors, while relying on the non-hydrolyzable silane to provide long-lasting hydrophobic protection, ultimately achieving the optimal balance of mechanical properties, weather resistance and processability.

[0026] In some embodiments of the present invention, the raw materials for preparing the vinylsilane-modified polylactic acid particles, by weight, are: 1 to 10 parts of vinylsilane, 80 to 100 parts of polylactic acid resin, 0.005 to 0.01 parts of initiator, and 1 to 2 parts of UV stabilizer.

[0027] According to a second aspect of the present invention, a method for preparing the vinylsilane-modified polylactic acid-based nonwoven fabric material is provided, comprising the following steps: mixing the vinylsilane-modified polylactic acid particles and the anti-aging resin particles and feeding them into a spunbonding device to obtain the vinylsilane-modified polylactic acid-based nonwoven fabric material by spunbonding.

[0028] In some embodiments of the present invention, the zone temperature of the spunbond equipment is 160–190°C.

[0029] In some embodiments of the present invention, the method for preparing the vinylsilane-modified polylactic acid granules includes: mixing the raw materials for preparing the vinylsilane-modified polylactic acid granules and then granulating them in a twin-screw extruder.

[0030] This invention employs melt blending grafting technology in a twin-screw extruder to chemically graft vinylsilane onto the PLA molecular backbone by controlling reaction conditions. First, during twin-screw extrusion, the easily hydrolyzable silane, under the action of an initiator, undergoes a condensation reaction between its alkoxy (-OR) groups and the resulting silanol groups (Si-OH) that condense with the carboxyl / hydroxyl groups at the PLA chain ends, forming stable Si-OC covalent bonds. This chemical bonding method solves the phase separation problem caused by physical blending. Simultaneously, the grafted silane side chains induce a more ordered arrangement of the PLA molecular chains through intermolecular interactions, increasing the crystal structure's orderliness, enhancing the material's mechanical strength, and further preventing moisture penetration due to the dense structure of the crystalline regions. By selecting specific combinations of vinylsilanes (synergistic effects of readily hydrolyzable and non-hydrolyzable silanes), precise performance control was achieved: readily hydrolyzable silanes (such as vinyltrimethoxysilane) endow the material with dynamic protective capabilities—when PLA is used in a humid environment, the Si-OH generated by the preferential hydrolysis of siloxane bonds forms new crosslinking points through secondary condensation, delaying the breakage of the PLA main chain; while non-hydrolyzable silanes (such as tetramethyltetravinylcyclotetrasiloxane) construct a permanent hydrophobic network, enabling the material to maintain a stable high contact angle. This synergistic "sacrifice-protection" dual mechanism allows the modified PLA to maintain biodegradability under composting conditions while simultaneously improving its hydrolysis resistance.

[0031] In some embodiments of the present invention, the method for preparing the vinylsilane-modified polylactic acid particles includes:

[0032] After mixing the initiator, vinyl silane and polylactic acid resin particles, the mixture was air-dried at room temperature for 8–24 hours and then granulated using a twin-screw extruder.

[0033] In some embodiments of the present invention, in the method for preparing vinylsilane-modified polylactic acid particles, the temperature of each section of the twin-screw extruder barrel is 160-200°C, and the screw rotation speed is set to 90-100 rpm.

[0034] In some embodiments of the present invention, the method for preparing the anti-aging resin particles includes: mixing the raw materials for preparing the anti-aging resin particles and then granulating them in a twin-screw extruder.

[0035] In some embodiments of the present invention, in the method for preparing the anti-aging resin particles, the temperature of each section of the twin-screw extruder barrel is 160-180°C, and the screw rotation speed is set to 90-100 rpm.

[0036] Polylactic acid (PLA), as an environmentally friendly bio-based material, has significant advantages but also suffers from obvious limitations such as brittleness and low toughness. Currently, the modification and preparation of PLA nonwoven fabrics are mostly achieved by introducing various auxiliaries. This method cannot fundamentally change the inherent structure of PLA, and excessive auxiliaries can also affect the spinning and web-forming properties of PLA. Reactive extrusion modification, on the other hand, can change the chemical structure of PLA in a relatively simple and inexpensive way, achieving fundamental performance control. Existing common PLA modification methods, such as blending with other polymers, copolymerizing PLA with other monomers, and adding plasticizers, all have certain drawbacks. However, since the mixing of different materials is achieved through physical means rather than covalent bonding, the compatibility between the blended components is poor, potentially leading to phase separation or weak interfacial interactions, resulting in poor stability of the resulting composite material. While copolymerization modification can obtain composite materials with multiple advantages by controlling the monomer ratio, improving material performance and functionality, its high cost and complex processes have prevented large-scale industrial production. Plasticizer modification is divided into two methods: modification with small-molecule plasticizers and modification with large-molecule plasticizers. The former, while showing significant toughening effects, suffers from high migration rates, easily leading to a decline in material performance. The latter, although exhibiting reduced migration rates, has unsatisfactory compatibility with PLA, sometimes making it difficult to achieve the expected modification effect. To avoid these difficulties, this invention employs a melt-blending grafting method in the PLA modification stage, grafting vinylsilane onto the polymer backbone. The addition of vinylsilane increases the orderliness and crystallinity of the PLA's crystal structure. This method can improve the hydrolysis resistance of PLA without sacrificing its biodegradability, making it a good choice for grafting modified PLA. It successfully avoids the drawbacks of traditional modification methods and ensures the performance of the final polylactic acid nonwoven fabric.

[0037] Polylactic acid (PLA) nonwoven fabrics are prone to degradation and embrittlement due to hydrolysis, leading to performance loss. This invention addresses this problem by grafting hydrophobic and tough vinylsiloxanes onto the PLA chain during the reactive extrusion process of PLA. The silanes, which are not easily hydrolyzed, contain hydrophobic groups such as low-polarity silicon-oxygen (Si-O) and silicon-carbon bonds. Grafting vinylsiloxanes onto the PLA chains using an initiator reduces the surface energy of the PLA nonwoven fabric, making it less likely to interact with water molecules. This imparts excellent hydrophobic properties to the PLA material, effectively delaying the penetration and hydrolysis of water into the PLA matrix, enhancing the material's anti-aging properties, and significantly extending its service life as an agricultural mulch film. In addition, although PLA inevitably undergoes hydrolysis leading to the breakage of PLA macromolecules, the carbon-oxygen-silicon bonds (CO-Si) in the hydrolyzable silane grafted onto the PLA main chain also undergo hydrolysis to generate certain active silanol groups (Si-OH). These groups condense under the action of water that has penetrated into the PLA matrix, thereby delaying the breakage of the PLA macromolecular network and thus delaying fiber disintegration, and extending the service life of PLA nonwoven fabrics.

[0038] According to a third aspect of the present invention, the application of a vinylsilane-modified polylactic acid-based nonwoven material in the preparation of biodegradable mulch films is proposed. Detailed Implementation

[0039] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0040] Example 1

[0041] This embodiment provides a vinylsilane-modified polylactic acid (PLA)-based nonwoven fabric material and its preparation method. The raw materials for preparing the vinylsilane-modified PLA-based nonwoven fabric material are shown in Table 1, and the preparation method is as follows:

[0042] S1. First, dissolve the initiator in vinyl silane, stir evenly, add PLA particles, let stand at room temperature for 8 hours to allow PLA to fully adsorb the modification solution, then feed the mixture into a twin-screw extruder, melt extrude and pelletize at a barrel temperature of 160°C and a screw speed of 90 rpm to obtain vinyl silane modified polylactic acid particles.

[0043] S2. Spinning grade PLA, antioxidant, and PBAT (melt index 10-20) are premixed evenly in a high-speed mixer, fed into a twin-screw extruder, melt-extruded and pelletized at 160°C (the temperature of the twin-screw extruder is gradually increased from 160-200°C from the inlet to the outlet) to obtain anti-aging resin granules.

[0044] S3. Mix the vinyl silane-modified polylactic acid granules obtained above with anti-aging resin granules, stir for 10 minutes until uniform, and put them into a spunbond equipment. Melt-spun into a web at a spinning temperature of 160°C (wherein the spinning temperature is divided into zones of 160°C, 170°C, 180°C, 190°C, and 200°C from the inlet to the outlet, with the temperature gradually increasing from the inlet to the outlet), a drafting wind speed of 0.5-1 m / s, and a web forming speed of 10 m / min. Then, reinforce it with hot rollers at 80°C and 0.5 MPa to finally obtain vinyl silane-modified polylactic acid-based nonwoven fabric material.

[0045] Examples 2-5

[0046] This embodiment provides a vinylsilane-modified polylactic acid-based nonwoven fabric material and its preparation method. The raw materials for preparing the vinylsilane-modified polylactic acid-based nonwoven fabric material are shown in Table 1, and the preparation method is the same as in Example 1.

[0047] Comparative Examples 1-2

[0048] This comparative example provides a vinylsilane-modified polylactic acid-based nonwoven fabric material and its preparation method. The raw materials for preparing the vinylsilane-modified polylactic acid-based nonwoven fabric material are shown in Table 1, and the preparation method is the same as that in Example 1.

[0049] Comparative Example 3

[0050] This comparative example provides a vinylsilane-modified polylactic acid-based nonwoven fabric material and its preparation method. The difference between this comparative example and Example 1 is that the vinyltrimethoxysilane content is 1 part, and the preparation method is the same as that of Example 1.

[0051] When the amount of easily hydrolyzable vinyltrimethoxysilane added in the comparative example is too small, the hydrophobicity of the material will decrease significantly due to insufficient silane grafting rate. Secondly, the crystallinity improvement effect will be weakened, resulting in a loose fiber network structure and a decrease in warp tensile strength. Due to the lack of sufficient easily hydrolyzable silane to build a dynamic protection mechanism, the performance retention rate of the material after 200 hours of xenon lamp aging will be greatly reduced.

[0052] Comparative Example 4

[0053] This comparative example provides a vinyl silane-modified polylactic acid-based nonwoven fabric material and its preparation method. The difference between this comparative example and Example 1 is that the vinyl silicone oil is 15 parts, and the preparation method is the same as that of Example 1.

[0054] When an excessive amount of non-hydrolyzable vinyl silicone oil is added in the comparative ratio, it will cause multiple deteriorations in the material properties. Excess silicone oil will significantly reduce the melt viscosity of the system, leading to unstable fiber stretching during spinning. Secondly, excessive silicone oil not only cannot participate in effective crosslinking, but also hinders the uniform dispersion of antioxidants in anti-aging resins. Uncrosslinked silicone oil will precipitate during subsequent processing and use, damaging the structural integrity and weather resistance of the material.

[0055] Comparative Example 5

[0056] This comparative example provides a vinylsilane-modified polylactic acid-based nonwoven fabric material and its preparation method. The difference between this comparative example and Example 1 is that the vinylsilane-modified polylactic acid particles in step S1 are obtained by mixing in an internal mixer instead of granulation by a twin-screw extruder.

[0057] Inaccurate temperature control in this comparative model leads to thermal degradation of PLA, making it difficult to achieve stable chemical bonding between silane and PLA. Unreacted silane (especially vinyl silicone oil) is prone to migration and precipitation, resulting in a significant decrease in the material's anti-aging properties.

[0058] Table 1. Composition of vinylsilane-modified polylactic acid-based nonwoven materials in the examples and comparative examples

[0059]

[0060]

[0061] Test Example 1

[0062] This test example performs the following performance tests on the vinylsilane-modified polylactic acid-based nonwoven fabric materials prepared in the examples and comparative examples. The results are shown in Table 2:

[0063] Mechanical property testing standards and methods: Tested according to GB / T 24218.3-2010 standard, sample size: 50mm*300mm, tensile rate: 300mm / min. Melt index was tested according to ASTM D1238, with the nonwoven fabric sample cut into pieces and fed into the melt index tester. Water contact angle testing was performed using a KRUSSDSA25 contact angle tester. A 2μl drop of distilled water was placed on the sample and held for 10 seconds, then the contact angle value of the nonwoven fabric sample was measured using the equipment's software.

[0064] Table 2. Performance Testing

[0065]

[0066]

[0067] As shown in Table 2 above, the tensile strength of all embodiments can reach 60N and the elongation can reach more than 110%, which shows good mechanical properties; after 200h xenon lamp aging, the tensile strength can reach 50N and the elongation can reach more than 90%, which shows good anti-aging properties.

[0068] The difference between the examples and Comparative Example 1 is that Comparative Example 1 only added anti-aging PLA resin and did not blend it with vinylsilane modified polylactic acid resin, while the examples blended and spun the two into nonwoven fabric. The comparison shows that the introduction of anti-aging PLA resin can improve the anti-aging performance of nonwoven fabric.

[0069] The difference between the Example and Comparative Example 2 is that Comparative Example 2 only added vinylsilane-modified polylactic acid resin and did not blend it with anti-aging PLA resin, while the Example blended the two and spun them into nonwoven fabric. The comparison shows that the introduction of anti-aging PLA resin can improve the toughness of nonwoven fabric and its toughness after aging.

[0070] The difference between Examples 1, 3, and 5 and Examples 2 and 4 is that Examples 2 and 4 did not introduce vinyl silicone oil. The comparison shows that the fiber water contact angle increased after the introduction of vinyl silicone oil, which can improve the hydrolysis resistance of nonwoven fabric.

[0071] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A vinylsilane-modified polylactic acid-based nonwoven fabric material, characterized in that, The raw materials for preparation include: vinylsilane-modified polylactic acid particles and anti-aging resin particles; The raw materials for preparing the vinylsilane-modified polylactic acid particles include: initiator, vinylsilane, and polylactic acid resin; The raw materials for preparing the anti-aging resin particles include: antioxidants, polylactic acid resin, butylene adipate and butylene terephthalate copolymers; The vinyl silanes include: readily hydrolyzable vinyl silanes and non-hydrolyzable vinyl silanes; The readily hydrolyzable vinylsilane includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(β-methoxyethoxy)silane. When the material undergoes hydrolysis during use, the Si in the readily hydrolyzable vinylsilane... O C bonds preferentially break to generate new silanol groups, which then recrystallize into Si via condensation reactions. O Si crosslinking points, thereby delaying the breakage process of the PLA main chain; The non-hydrolyzable vinyl silanes include at least one of tetramethyltetravinylcyclotetrasiloxane, divinyltetramethyldisiloxane, and vinyl silicone oil. The non-hydrolyzable vinyl silanes possess stable Si... O Si and Si The C-bond structure forms a hydrophobic barrier in the material, enabling the material to maintain a stable high contact angle and effectively blocking the penetration of water molecules.

2. The vinylsilane-modified polylactic acid-based nonwoven fabric material according to claim 1, characterized in that, The raw materials for preparing the vinylsilane-modified polylactic acid particles also include UV stabilizers.

3. The vinylsilane-modified polylactic acid-based nonwoven fabric material according to claim 1, characterized in that, The raw materials for preparation, by weight, include: 20-100 parts of vinylsilane-modified polylactic acid particles and 1-80 parts of anti-aging resin particles.

4. The vinylsilane-modified polylactic acid-based nonwoven fabric material according to claim 2, characterized in that, The raw materials for preparing the vinylsilane-modified polylactic acid particles, by weight, are: 1-10 parts of vinylsilane, 80-100 parts of polylactic acid resin, 0.05-0.1 parts of initiator, and 0.5-1 parts of UV stabilizer.

5. A method for preparing a vinylsilane-modified polylactic acid-based nonwoven fabric material as described in any one of claims 1 to 4: characterized in that, Includes the following steps: The vinylsilane-modified polylactic acid particles and the anti-aging resin particles are mixed and then fed into a spunbonding device to obtain a vinylsilane-modified polylactic acid-based nonwoven fabric material.

6. The preparation method according to claim 5, characterized in that, The zone temperature of the spunbond equipment is 160~190℃.

7. The preparation method according to claim 5, characterized in that, The method for preparing the vinylsilane-modified polylactic acid granules includes: mixing the raw materials for preparing the vinylsilane-modified polylactic acid granules and then granulating them in a twin-screw extruder.

8. The preparation method according to claim 5, characterized in that, The method for preparing the anti-aging resin particles includes: mixing the raw materials for preparing the anti-aging resin particles and then granulating them in a twin-screw extruder.

9. The application of the vinylsilane-modified polylactic acid-based nonwoven material according to any one of claims 1 to 4 in the preparation of biodegradable mulch films.

Citation Information

Patent Citations

  • PLA / PBAT biodegradable composite material and preparation method thereof

    CN103254597A

  • Modified polylactic acid-based non-woven fabric material as well as preparation method and application thereof

    CN116856116A